2005
DOI: 10.1177/0021943604272028
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Information Seeking: Understanding How Traits Influence Information-Seeking Behaviors

Abstract: Organizational newcomers go through various socialization processes before becoming organizational veterans. Information seeking (a self-socialization process) involves newcomers' proactively seeking new information, most times to reduce uncertainty. This study assessed how personality traits, specifically, Costa and McCrae's Big Five, affect this process. Multiple regression analyses indicate that certain traits influence information seeking directly and via the mediation of social costs. Of particular note a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 58 publications
2
65
0
7
Order By: Relevance
“…At the same time, they recognized that conscientious individuals, because of the strong "industrious element" of conscientiousness that is about being hardworking and dependable (Roberts, Chernyshenko, Stark, & Goldberg, 2005), will want to achieve a good fit within the organization. Other studies have similarly found conscientiousness to predict proactive PE-fit behaviors, such as career planning (Carless & Bernath, 2007) and information seeking (Tidwell & Sias, 2005).…”
Section: Individual Differences In Personality and Valuesmentioning
confidence: 81%
“…At the same time, they recognized that conscientious individuals, because of the strong "industrious element" of conscientiousness that is about being hardworking and dependable (Roberts, Chernyshenko, Stark, & Goldberg, 2005), will want to achieve a good fit within the organization. Other studies have similarly found conscientiousness to predict proactive PE-fit behaviors, such as career planning (Carless & Bernath, 2007) and information seeking (Tidwell & Sias, 2005).…”
Section: Individual Differences In Personality and Valuesmentioning
confidence: 81%
“…Previous studies on personality and information search behavior have focused on the influence personality has on the use of word of mouth , information behavior in general (Heinstrom, 2006;Hyldegard, 2009;Tidwell & Sias, 2005), decision process (Horton, 1979), and information processing (Schaninger & Sciglimpaglia, 1981). McElroy, Hendrickson, Townsend, and Demarie (2007) argue for the use of the BFF in information studies, as these are less mutable compared to other personal variables.…”
Section: Tourist Internet Search Behavior and Personalitymentioning
confidence: 99%
“…age, income) that might change over time. Within the information-search context, personality has been applied to explain students' information searching (Heinstrom, 2005), the use of word-of-mouth (Mowen, Park, & Zabla, 2007), and the preference for information type (Tidwell & Sias, 2005) with a significant relationship being observed in each case. Despite these findings confirming the influence of personality on informationsearch behavior, few have examined its influence in tourism settings, where the Internet is believed to be an influential information source.…”
Section: Introductionmentioning
confidence: 99%
“…For example, review of antecedents and outcomes of socialization, Bauer et al (2007) reported that information gathering, which could be realized through the availability of knowledge sharing, is a significant antecedent of socialization. Knowledge means reduced uncertainty (Iqbal, Toulson, & Tweed, 2011) and contributes to self-socialization (Tidwell & Sias, 2005).…”
mentioning
confidence: 99%